2022
DOI: 10.1088/1361-6439/ac6ebf
|View full text |Cite
|
Sign up to set email alerts
|

Biocompatible bonding of a rigid off-stoichiometry thiol-ene-epoxy polymer microfluidic cartridge to a biofunctionalized silicon biosensor

Abstract: Attachment of biorecognition molecules prior to microfluidic packaging is advantageous for many silicon biosensor-based lab-on-a-chip devices. This necessitates biocompatible bonding of the microfluidic cartridge, which, due to thermal or chemical incompatibility, excludes standard microfabrication bonding techniques. Here, we demonstrate a novel processing approach for a commercially available, two-step curable polymer to obtain biocompatible UVA-bonding of polymer microfluidics to silicon biosensors. Biocomp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 34 publications
0
4
1
Order By: Relevance
“…2C). The measured angle exceeds the reported values of 67°for standard cured oste322 as published by Sandström et al 71 and 73 ± 2°(for oste327) and 70 ± 3°(for oste322) reported by Zhou et al 37 For reverse cured oste322, 72 the CA was found to be approximately 80°(ranging from 73°to 85°) and 96°for OSTE-80. 41 The increase in the contact angle measured in this study could be attributed to the alteration in the fabrication process of the oste322 inserts, which were subjected to a heating procedure before their removal from the PDMS mould.…”
Section: Materials Properties Of Oste322 Insertscontrasting
confidence: 54%
See 1 more Smart Citation
“…2C). The measured angle exceeds the reported values of 67°for standard cured oste322 as published by Sandström et al 71 and 73 ± 2°(for oste327) and 70 ± 3°(for oste322) reported by Zhou et al 37 For reverse cured oste322, 72 the CA was found to be approximately 80°(ranging from 73°to 85°) and 96°for OSTE-80. 41 The increase in the contact angle measured in this study could be attributed to the alteration in the fabrication process of the oste322 inserts, which were subjected to a heating procedure before their removal from the PDMS mould.…”
Section: Materials Properties Of Oste322 Insertscontrasting
confidence: 54%
“…For reverse cured oste322, 72 the CA was found to be approximately 80° (ranging from 73° to 85°) and 96° for OSTE-80. 41 The increase in the contact angle measured in this study could be attributed to the alteration in the fabrication process of the oste322 inserts, which were subjected to a heating procedure before their removal from the PDMS mould.…”
Section: Resultsmentioning
confidence: 95%
“…Reversible bonding techniques for access to electrodes may therefore be used. Recently, alternative room temperature bonding methods, which can also be applied to EC devices, have been demonstrated [35]. For size critical applications, the total footprint including contact pads can be an issue.…”
Section: Design and Fabrication Of Microfluidics Integrated With Elec...mentioning
confidence: 99%
“…Due to their controllable mechanical properties, and their ability for reshaping surface functionalization, and dry-bonding, dualcuring materials have become an interesting class of materials for advanced applications such as shape memory materials, [1,2] essential element for the detection of specific analytes in microfluidic analysis. The bio-functionalization of channel surfaces can be carried out by bonding of the open channel to a readyfor-use biosensor [17,18] or by direct biofunctionalization of the microchip material. [19] For successful biofunctionalization, the channel material often needs an additional treatment such as coating of a linker with sufficient interaction or direct immobilization of the biomolecule onto the surface.…”
Section: Introductionmentioning
confidence: 99%